Kajian Kritis atas Hubungan Pancasila dengan Prinsip Hukum Internasional tentang Keadilan dan Kesetaraan - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Alfia Nur Khasanah; Fina Amalia Nadi; Lulu’ah Ukhti Isnaini (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to explore and analyze the relationship between Pancasila, as the foundation of the Republic of Indonesia, and international principles of justice and equality. Pancasila, which consists of five precepts that reflect the basic values of the Indonesian nation, is expected to serve as a guideline in the application of the principles of social justice and equal rights in the international context. This study uses an analytical approach to evaluate how Pancasila aligns with various international conventions and standards related to human rights and social justice. It also discusses the challenges and opportunities in integrating Pancasila values with global norms, as well as its impact on Indonesia's public policy and international relations. The results show that while there is significant alignment between Pancasila and international principles on justice and equality, there are some challenges in its implementation that need to be addressed to ensure better harmonization between national and international norms.